2015
DOI: 10.1007/s12011-015-0447-8
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging Biomarkers of Bone Damage Induced by Environmental Level of Cadmium Exposure in Male Rats

Abstract: Cadmium (Cd) can induce bone loss and osteoporosis. Histologic methods have shown that Cd can induce microarchitecture change of the trabecular bone. The aim of this study is to evaluate the imaging biomarkers of osteoporosis induced by Cd using micro-computed tomography (micro-CT). Twenty-four male Sprague-Dawley rats were randomly divided into four groups that were exposed to Cd via drinking water at concentrations of 0, 2, 10, and 50 mg/L for 3 months. Before sacrifice, micro-CT scanning was performed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Our study showed a significant decrease in BMD as well as in %BV/TV parameters accompanied by a significant increase in the trabecular separation (Tb.Sp) in the distal femur of adult rats at PND70. Likewise, several authors have noted similar results by exposing 60-day-old rats to 50mg Cd/L for three months [43] or following chronic exposure to male rats during development [44,45]. We think that the decrease in BMD noted in our study partly explains the decrease in Ca content in the femurs of adult rats at PND70.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed a significant decrease in BMD as well as in %BV/TV parameters accompanied by a significant increase in the trabecular separation (Tb.Sp) in the distal femur of adult rats at PND70. Likewise, several authors have noted similar results by exposing 60-day-old rats to 50mg Cd/L for three months [43] or following chronic exposure to male rats during development [44,45]. We think that the decrease in BMD noted in our study partly explains the decrease in Ca content in the femurs of adult rats at PND70.…”
Section: Discussionsupporting
confidence: 89%
“…Before sacrifice, MicroCT examinations (Ge eXplore, GE healthcare, United States) was performed in all rats as previous studies described ( Chen et al, 2013 ; Tang et al, 2016 ). Briefly, rats were placed on the scanning platform after anaesthetizing (7.0% chloral hydrate, 0.5 ml/100 g body weight).…”
Section: Methodsmentioning
confidence: 99%
“…Osteoclast formation in tibia was identified by using TRAP staining as previous study described ( Chen et al, 2013 ; Tang et al, 2016 ). Briefly, the sections were treated as the following procedures: incubating in oven at 52°C for one hour, dewaxing by using dimethylbenzene, then hydrating through a series of descending ethanol solution (100–40%).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the Pb body burden is in mineralizing tissues (bones and teeth) [34]. The fact that Cd and Pb have a comparable radius to Ca ions means that both toxic metals can lead to bone damage by displacing Ca ions [11,35]. The International Agency for Research on Cancer (IARC) has classified Cd as carcinogenic to humans (Group 1), while inorganic Pb has been classified as probably carcinogenic to humans (Group 2A) based on limited evidence in humans and sufficient evidence in animals [21,22,36].…”
Section: Introductionmentioning
confidence: 99%